Drosophila vap-33 is required for axonal localization of dscam isoforms. - Yang, Z.; Huh, S.U.; Drennan, J.M.; Kathuria, H.; Martinez, J.S.; Tsuda, H.; Hall, M.C.; Clemens, J.C. (Journal of Neuroscience, 2012)
Mutations in VAPB have been identified in a familial form of amyotrophic lateral sclerosis (ALS), and reduced VAPB levels have been found in patients with sporadic ALS. Vap protein family members from different species and cell types have been implicated in a number of cellular functions, but how Vap dysfunction in neurons and/or muscles contributes to motor neuron degeneration and death is poorly understood. Using Drosophila as a model organism, we show that Vap physically interacts with and affects the axonal functions of the Down syndrome cell adhesion molecule (Dscam). Dscam is a cell-surface receptor involved in axon and dendritic patterning and neuron self-recognition and avoidance. Alternative splicing of the Dscam transcript leads to the production of Dscam isoforms that contain one of two possible transmembrane (TM) domain and flanking sequences that either restrict the isoform to dendrites and cell bodies (TM1) or target the isoform to axon processes (TM2). We find that Vap specifically interacts with Dscam isoforms that contain the TM2 cytoplasmic juxtamembrane flanking sequences. Using loss-of-function genetics, we further show that Vap is required for localization of Dscam isoforms containing TM2 to axons and that Vap loss suppresses Dscam gain-of-function axon phenotypes. We propose that Vap function is required in neurons to selectively traffic proteins to axons, and disruption of this function may contribute to the pathology of ALS.